Water‐soluble Lignosulfonates: Structure, Preparation, and Application. Issue 13 (4th April 2023) - Tang, Tao; Fei, Junhao; Zheng, Yi; Xu, Jian; He, Huiwen; Ma, Meng; Shi, Yanqin; Chen, Si; Wang, Xu
Abstract: As one of the key raw materials that replace petroleum materials in today's world, biomass resources could be regarded as a promising resource. Currently, lignin and its derivatives are the only lignocellulosic biomass found to possess aromatic rings. Extending the application area of lignin requires overcoming the limitations of its low hydrophilicity. Sulfonation process becomes the most effective method for preparing lignosulfonates. An analysis of the mechanisms by which different lignosulfonates are prepared. It compared the effects of various modification methods on charge density and sulfonate group content in lignosulfonates. It also examined how different separation techniques affect the properties of lignosulfonates. As a result of being more water‐soluble, there is also a review of cutting‐edge research in the fields of energy, medicine, and agriculture. Also, the possible uses of lignosulfonate are talked about, and ideas are given for how this compound could be improved in the future. Abstract : Lignosulfonates are derived from plant tissue, which makes them biocompatible. The aromatic ring structure and the special sulfonic acid group make the lignin sulfonate have the advantages of good hydrophilicity, high charge density, and high surface activity. These advantages promote its many applications in drug delivery, biomass conversion, energy, agriculture, and other fields.